Pelatihan Penguatan Tata Kelola Pemerintahan Desa Masa Pandemi - Rindawati, Septi; Astarika, Bella; Amelinda, Amelinda; Aprisyal, Tri; Sundari, sangkut Dwi (Universitas Dehasen Bengkulu, 2021)
The impact of the Covid 19 pandemic outbreak in Indonesia in general has affected all sectors of people's lives, one of which is community services. People are restricted from carrying out activities in public spaces, and limiting office operating licenses, as well as limiting employees who enter the office, only 50% of the number of employees are allowed, making public services, experience obstacles, The purpose of the study was to find out innovative and collaborative local governance during the Covid 19 pandemic obstacles and efforts to overcome these obstacles. The method used is descriptive qualitative with an inductive approach. Results and conclusions. Before the Covid 19 Pandemic outbreak, services were carried out face-to-face, but with the Covid 19 pandemic outbreak, services were changed by using online applications connected to the internet network, services in the form of on-line can be said to be successful, because there is public satisfaction with these services. as for the obstacles that occur are in the form of networks, inadequate facilities and limited Human Resources.